Multi-solid model modified to predict paraffin precipitation in petroleum fluids at high temperatures and pressures - Escobar Remolina, Juan Carlos M.; Ortiz, Wilson Barrios; Santoyo Ramírez, Gildardo (CT&F - Ciencia, Tecnología y Futuro, 2009)
Athermodynamic structure has been modified in order to calculate cloud point, fluidity and amount of precipitated wax under a wide range of temperature conditions, composition, and high pressures. The model is based on a combination of ideal solution concepts, fluid characterization, and formation of multiple solid phases using Cubic State Equations. The experimental data utilized for testing the prediction capacity and potentiality of a model exhibit different characteristics: continuous series synthetic systems of heavy alkanes, discontinuous series, and dead or living petroleum fluids with indefinite fractions such as C7+, C10+, C20+, and C30+. The samples were taken from the literature, petroleum fluids from the main Colombian reservoirs, and some samples of Bolivian fluids. Results presented in this paper show the minimum standard deviations between experimental data and data calculated with a model. This allows a progress in decision-making processes for flow assurance in reservoirs, wells, and surface facilities in the petroleum industry.